Джузеппе Верди: монография / Л. Соловцова - Соловцова Любовь Андреевна (Музыка, 1986)
Экземпляры: ЧЗ (20180824) / Инвентарный номер: 15979 / Цена: 1.70 / Сис.шифр: 85.313(4Ит)5-8 (Верди) / Авт.знак: С60 / ГРНТИ: 18 / ББК: 85.313(4Ит)5-8 (Верди)